Linguistic Sexism On The Portrayal Of Female And Male Celebrities In News Coverage - Sherina Brenda Sopyani; Ni Made Suwari Antari; I Komang Sumaryana Putra (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
News articles always play a vital role, it has a broad impact and is gradually becoming a part of daily life. Celebrity lifestyle also draws attention and quite eager to be read, and this paper aims to investigate the expression of linguistic sexism against female celebrities in the various news media. Adopting a feminist stylistic within word level and discourse level, this paper attempt to analyze 22 written news. The selected features at the word level include transitivity which requires naming categories and material actor versus material goal. While the discourse level include modality and passivization. It reveals that linguistic sexism is present in celebrity news coverage, with several subtle forms of sexism.